Peran Inovasi Teknologi dalam Transformasi Industri Rokok: Dampaknya Terhadap Produksi, Distribusi, dan Penggunaan Produk Rokok - Agustin, Aisyah Sovia; Maghfiroh, Putri Nisful Lailatul; Firdaus, Muhammad; Alfarisy, Salman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Generation Z, born between 1997 and 2012, exhibits a significant trend in adopting vape or electronic cigarettes as an alternative to conventional tobacco cigarettes. This study aims to investigate the influence of vape use on the tobacco industry in Indonesia, focusing on production, distribution, and consumer behavior. The research employs a qualitative approach through literature review and interviews. Data were collected from scholarly literature, primary data analysis via questionnaires, and direct interviews with cigarette manufacturers and vape users. Findings indicate that Generation Z tends to adopt vape due to its perceived modernity, diverse flavors, and perceived safety compared to traditional cigarettes. However, vape use also faces negative perceptions from some sectors of society regarding potential health impacts. Moreover, despite the rising popularity of vape, traditional tobacco cigarettes remain favored due to habit, tranquility, and personal preferences.